PENERAPAN SISTEM TRANSAKSI NON TUNAI TERHADAP AKUNTABILITAS KINERJA MANAJERIAL - Ashari Lintang Yudhanti (Behavioral Accounting Journal, 2018)
Successfully of performance is determined by the effectiveness and efficiency of an organization's managerial activities. The performance is a management tool to improve organizational accountability. Non- cash payment transaction system is present to answer the needs of the organization today as an effort to encourage transparency and financial accountability. The purpose of this study is to test the influence of implementation of non-cash transaction system to accountability, accountability effect on managerial performance, influence implementation of non-cash transaction system to managerial performance, and influence of implementation of non-cash transaction system to managerial performance through accountability. The population of this research is the staff of ITS Surabaya who operate the non-cash transaction system, while the sample used is 50 employees, with using probability sampling technique. The data used in this study is the primary data through the distribution of questionnaires to employees. Analysis technique in this research is Partial Least Square (PLS). The results of this study indicate that implementation of non-cash transaction system has a significant effect on accountability, accountability has a significant effect on managerial performance, implementation of non-cash transaction system has significant effect directly on managerial performance, and implementation of non-cash transaction system has significant effect on managerial performance through accountability. thus, the implementation of non-cash transaction system, supports business process on ITS Surabaya so it can more effectively and efficientlySmall and Medium Enterprises (SMEs) have limited resources, therefore it is necessary to mediate not only the understanding of taxation, but can help to develop business management, so that SMEs get the ease of developing the business and will have a positive impact on SME players. Thus taxpayers will respond positively to tax pay compliance. This research will continue the development of SME governance. However, the first year of this study will first see the quality of education and understanding of the taxpayer, with the aim is, to determine the effect of the quality of extension services tax and tax understanding of the taxpayer compliance response. The method used is an eplanatory survey of 100 SMEs in Yogyakarta. To get data using questionnaire. By sending a questionnaire by post or e-mail, many respondents do not return it, then do it directly collect from the respondent. Data testing is done by Partial Least Square (PLS) method. PLS does not assume any particular distribution for parameter estimation, so no parametric technique is required to test parameters. The result of this research conclude that the quality of service of tax service influence but very low to taxpayer compliance, while the understanding of taxpayer has a significant effect on taxpayer compliance.